Green Building Construction: A Systematic Review of BIM Utilization - Yu Cao; Syahrul Nizam Kamaruzzaman; Nur Mardhiyah Aziz (Buildings, 2022)
As a multi-function method, Building Information Modeling (BIM) can assist construction organizations in improving their project’s quality, optimize collaboration efficiency, and reduce construction periods and expenditure. Given the distinguished contributions of BIM utilization, there is a trend that BIM has significant potential to be utilized in the construction phase of green buildings. Compared with traditional buildings, green buildings have more stringent requirements, including environmental protection, saving energy, and residents’ comfort. Although BIM is deemed an effective method to achieve the abovementioned requirements in the construction process of green buildings, there are few systematic reviews that explore the capabilities of BIM in the construction phase of green buildings. This has hindered the utilization of BIM in the construction of green buildings. To bridge this research gap and review the latest BIM capabilities, this study was developed to perform a systematic review of the BIM capabilities in the construction phase of green buildings. In this systematic review, the PRISMA protocol has been used as the primary procedure for article screening and review. The entire systematic review was performed from January 2022 to April 2022. In this process, 165 articles were included, reviewed, and discussed. Web of Science (WoS) and Scopus were adopted as the databases. Through this systematic review, it can be identified that BIM capabilities have significant advantages in project quality improvement, lifecycle data storage and management, collaboration optimization, planning, and schedule management optimization in the construction phase of green buildings. Through the discussion, it can be concluded that BIM utilization can be adopted from the pre-construction phase to the post-construction stage in the green building construction process. Besides these, the barriers to BIM utilization in the green building construction phase are also revealed in the discussion section, including the non-uniform data format, insufficient interactivity, ambiguous ownership, insufficient BIM training, and hesitation toward BIM adoption. Moreover, the challenges and future directions of BIM utilization in green building construction are identified. The findings of this study can facilitate construction personnel to be acquainted with BIM capabilities in the construction of green buildings to promote the utilization and optimization of BIM capabilities in the green building construction process.